Tissue and serum biomarkers as prognostic variables in endometrioid-type endometrial cancer - Gadducci, Angiolo; Cosio, Stefania; Genazzani, Andrea Riccardo (Critical reviews in oncology/hematology, 2011)
FIGO stage, tumor grade, depth of myometrial invasion, lymph-vascular space status and lymph node status are the most important clinical-pathological prognostic variables for endometrioid-type endometrial carcinoma. In the last years, several investigations have assessed different biological variables in tissue and serum samples from patients with this malignancy in order to detect biomarkers able to predict the clinical outcome. The present paper reviewed the literature data about the prognostic relevance of mutational status and/or immunohistochemical expression of p53, PTEN, PIK3, mTOR, β-catenin, k-ras and RASSF1A, microsatellite instability, vascular endothelial growth factor expression, DNA aneuploidy, and serum assay of CA125 and other tumor associated antigens. Tissue and serum biomarkers could be used, in addition to the conventional clinical-pathological variables, for the stratification of patients into categories with different risk of recurrence to better tailor adjuvant treatment.